2003
DOI: 10.1080/00365540310004027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Tuberculous Lymphadenitis in Butajira, Rural Ethiopia

Abstract: Tuberculous lymphadenitis (TBLN) is a diagnostic challenge in sub-Saharan Africa, where there is a high rate of human immunodeficiency virus (HIV) infection. This study aimed to find ways to improve the diagnosis in Butajira, rural Ethiopia, where TBLN constitutes 40% of the total tuberculosis (TB) diagnosis. Among 147 clinically suspected cases, 107 (72.8%) were confirmed as TBLN by fine-needle aspiration (FNA) cytology and acid-fast bacillus (AFB) smear examination. Of the remaining 40 cases, denoted non-tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 12 publications
6
29
0
1
Order By: Relevance
“…The presence of granulomas in 24 of 49 culture-negative patients might be due to infection by either tuberculous or nontuberculous mycobacteria (NTM) which were not adequately detected by the sample culture. Our results are compatible with a study conducted in Butajira, Southern Ethiopia, which reported that in 23 patients identified with nontuberculous lymphadenitis by cytology, PCR confirmed the presence of MTC in 15 and in the remaining 8, MTC was not detected [21]. Moreover, a recent study conducted at AHRI using FNAs and biopsies of 117 TBLN patients from eastern, central and northern Ethiopia identified only M. tuberculosis as the etiological agent of TBLN by using the RD10 primers system [22].…”
Section: Discussionsupporting
confidence: 82%
“…The presence of granulomas in 24 of 49 culture-negative patients might be due to infection by either tuberculous or nontuberculous mycobacteria (NTM) which were not adequately detected by the sample culture. Our results are compatible with a study conducted in Butajira, Southern Ethiopia, which reported that in 23 patients identified with nontuberculous lymphadenitis by cytology, PCR confirmed the presence of MTC in 15 and in the remaining 8, MTC was not detected [21]. Moreover, a recent study conducted at AHRI using FNAs and biopsies of 117 TBLN patients from eastern, central and northern Ethiopia identified only M. tuberculosis as the etiological agent of TBLN by using the RD10 primers system [22].…”
Section: Discussionsupporting
confidence: 82%
“…32,33 Expertise in excisional biopsy is often limited in developing countries. 34 Histology of excisional biopsy shows in over 90% evidence of caseous granulomas. 35 Culture of biopsy samples have shown positive culture rates in 77-90%.…”
Section: Tuberculous Lymphadenitismentioning
confidence: 99%
“…Culture alone was relied upon in seven studies (44%) and culture plus anti-T therapy treatment, histology or X-ray in six studies. The remaining two did not include culture as part of the reference standard but relied on cytology alone 34 or histology plus an anti-TB therapy trial. 217 …”
Section: Reference Standardsmentioning
confidence: 99%
“…This observation was comparable to finding of a study where 67.5% cervical, 9% axillary and 6.4% inguinal lymph node involvements were reported 15 . A study in Butajira, Ethiopia, revealed that 88(82.2%) of 105 tuberculous lymphadenitis cases had cervical involvement 16 .…”
Section: Discussionmentioning
confidence: 99%